HYDROACOUSTIC EX-SITU TARGET STRENGTH MEASUREMENTS OF SHRIMP SCAD ALEPES DJEDDABA (FORSSKÅL, 1775) IN VIET NAM - Nghia, Nguyen Viet (Vietnam Journal of Marine Science and Technology, 2014)
Shrimp scad Alepes djeddaba is an important small pelagic species in Viet Nam, which contributes a large part of the fisheries resources. The main objective of this study was to establish an empirical estimate of the relation between target strength and length of shrimp scad at 38kHz, which can be served for assessments of these resources using hydroacoustic surveys. The ex-situ experiments were set up in 160 m³ measurement pen, using SIMRAD EK-60 split-beam echo-sounder. Total of 83 individual of fish were monitored in six sets of experiments. The TS-to-length relationship of shrimp scad was determined as TS=20log(L) - 65.4. In consideration of biological effect, the TS-to-length relationship can be revised as TS = 20log(L) - 77.9 - 6.0CF + 0.5Li + 1.5GSi + 2.8SBi. The most influenced factor to the TS-to-length relation could be condition factor > swimbladder index > gonadosomatic index > liver index.